2021
DOI: 10.1038/s41598-021-86840-9
|View full text |Cite
|
Sign up to set email alerts
|

Superposition principle applies to human walking with two simultaneous interventions

Abstract: Gait rehabilitation therapies provide adjusted sensory inputs to modify and retrain walking patterns in an impaired gait. Asymmetric walking is a common gait abnormality, especially among stroke survivors. Physical therapy interventions using adaptation techniques (such as treadmill training, auditory stimulation, visual biofeedback, etc.) train gait toward symmetry. However, a single rehabilitation therapy comes up short of affecting all aspects of gait performance. Multiple-rehabilitation therapy applies sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…The coe cients corresponding to the second perturbation revealed that approximately 85% of the contribution of the constituent intervention could be predicted from the control interventions. This is a close approximation of the coe cients determined in a previous study that applied the same interventions simultaneously [32]. In addition, coe cients representing the impact of the rst intervention on acquired asymmetry during adaptation-2 were signi cantly (and predictably) smaller.…”
Section: Interventional Contribution To Gait Asymmetry Re-acquisitionsupporting
confidence: 73%
See 3 more Smart Citations
“…The coe cients corresponding to the second perturbation revealed that approximately 85% of the contribution of the constituent intervention could be predicted from the control interventions. This is a close approximation of the coe cients determined in a previous study that applied the same interventions simultaneously [32]. In addition, coe cients representing the impact of the rst intervention on acquired asymmetry during adaptation-2 were signi cantly (and predictably) smaller.…”
Section: Interventional Contribution To Gait Asymmetry Re-acquisitionsupporting
confidence: 73%
“…The previous ARAC study found that adaptation to SBT and ARAC exhibit additive effects in spatiotemporal and kinetic gait parameters when both therapies were applied simultaneously [32]. This superposition indicates that the adaptation mechanisms (i.e., "sensorimotor feedback" and "strategic") associated with these interventions are likely to run concurrently, allowing the participant to simultaneously bene t from the two interventions.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…The ability to predict a patient's response to the training session (session two) allows for informed decisions to be made upon completion of the evaluation session (session one). Not all participants respond to all forms of gait intervention, as has been demonstrated in rhythmic cueing experiments for step time rehabilitation [13]. Therefore, this predictive model could potentially give examiners the ability to identify possible split-belt training non-responders quickly.…”
Section: Predictive Model For Session Twomentioning
confidence: 99%